Adult Health and Early Life Adversity: Behind the Curtains of Maternal Care Research - Dumas, Theodore C. (Frontiers in Physiology, 2022)
The quality of one’s adult health and the chances of maintaining cognitive ability in aging stem directly from the quality of care one receives as an infant. Formal studies of maternal care can be traced back at least a century. Revelations of behavioral outcomes after maternal deprivation in primates were followed by discoveries of systemic and brain growth factors mediated by the caregiver-offspring relationship in rodents. More recently, much of the genetic/epigenetic bases of maternal care has been defined and positively linked to adult health and cognitive ability in senescence. The history of this field is both tragic and fascinating. The early primate work, while informative, was abusive. The initial rodent work was ridiculed before its importance was recognized. The final lesson learned is that infant/toddler care matters a lot. Today, we have a better understanding of the biology underlying maternal care and its transmission across generations as well as a scientific basis for massaging premature infants and hugging our children.